2019
DOI: 10.1002/bdr2.1606
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association studies of structural birth defects: A review and commentary

Abstract: Background While there is strong evidence that genetic risk factors play an important role in the etiologies of structural birth defects, compared to other diseases, there have been relatively few genome‐wide association studies (GWAS) of these conditions. We reviewed the current landscape of GWAS conducted for birth defects, noting novel insights, and future directions. Methods This article reviews the literature with regard to GWAS of structural birth defects. Key defects included in this review include oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 110 publications
0
25
0
Order By: Relevance
“…Pedigree studies demonstrate both autosomal-dominant and autosomal-recessive patterns of inheritance (Brown et al, 2013;Piceci et al, 2017;Chen et al, 2018;Lupo et al, 2019; FIGURE 2 | Protein-to-protein interactions of candidate genes with known microtia-atresia associated pathways. (A) HOXA4 directly interacts with RARA of the RA pathway, detected in three families (II, III, V); (B) TBX10 interacts directly or indirectly with WINT11 of the Wnt pathway; (C) AMER1 interacts indirectly with WINT3A of the Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Pedigree studies demonstrate both autosomal-dominant and autosomal-recessive patterns of inheritance (Brown et al, 2013;Piceci et al, 2017;Chen et al, 2018;Lupo et al, 2019; FIGURE 2 | Protein-to-protein interactions of candidate genes with known microtia-atresia associated pathways. (A) HOXA4 directly interacts with RARA of the RA pathway, detected in three families (II, III, V); (B) TBX10 interacts directly or indirectly with WINT11 of the Wnt pathway; (C) AMER1 interacts indirectly with WINT3A of the Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of high heritability, as high as 70–90%, in certain types of congenital heart anomalies (Cripe, Andelfinger, Martin, Shooner, & Benson, 2004; Hinton et al, 2007; McBride et al, 2005). Genome wide association and whole exome sequencing studies have identified hundreds of genes and candidate genes/loci involved with isolated CHD (Lalani & Belmont, 2014; Li et al, 2017; Lupo, Mitchell, & Jenkins, 2019; Page et al, 2019) however, most genes account for a small percentage of cases and there remains a significant number with no confirmed genetic etiology.…”
Section: Discussionmentioning
confidence: 99%
“…ES, which provides sequence information from the coding regions of known genes in the human genome, also holds promise for improving the rate of genetic diagnosis. Since most of the conditions associated with omphalocele may not be included in specific gene panels, ES may be effective in identifying a diagnosis in cases with normal karyotype and/or CMA 51 . Recent studies looking at prenatal exomes do not specifically report cases of omphalocele, therefore the exact utility of using ES in cases of omphalocele remains unclear 52 …”
Section: Introductionmentioning
confidence: 99%